Two new sesquiterpenes from the leaves of Nicotiana tabacum and their anti-tobacco mosaic virus activities. Issue 22 (16th November 2016) - Shen, Qinpeng; Xu, Xingmeng; Liu, Chunbo; Zhao, Wei; Xiang, Nengjun; Chen, Yongkuan; Miao, Mingming; Liu, Zhihua; Yang, Guangyu
Abstract: Two new sesquiterpenes, nicotianasesterpenes A and B (1 and2 ), together with five known sesquiterpenes (3–7 ) were isolated from the leaves of Nicotiana tabacum . Their structures were determined mainly by spectroscopic methods, including extensive 1D- and 2D-NMR techniques. The anti-tobacco mosaic virus (anti-TMV) activities of compounds1–7 were evaluated. The results revealed that compound1 exhibited high anti-TMV activities with inhibition rates of 33.6%. This rate is high than that of positive control. The other compounds also showed potential activities with inhibition rates in the range of 18.8–28.4%, respectively. Graphical abstract: The structures of compounds1 –2.